Robotic-assisted anatomic anterior cruciate ligament reconstruction: a comparative analysis of modified transtibial and anteromedial portal techniques in cadaveric knees - Zhang, Ling; Lin, Jinpeng; Zhao, Xuan; Liu, Mingwei; Hou, Yao; Zhang, Yu; Zhao, Jinzhong; Wang, Shaobai (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: This study employed surgical robot to perform anatomic single-bundle reconstruction using the modified transtibial (TT) technique and anteromedial (AM) portal technique. The purpose was to directly compare tunnel and graft characteristics of the two techniques. Methods: Eight cadaveric knees without ligament injury were used in the study. The modified TT and AM portal technique were both conducted under surgical robotic system. Postoperative data acquisition of the tunnel and graft characteristics included tibial tunnel position, tunnel angle, tunnel length and femoral tunnel-graft angle. Results: The mean tibial tunnel length of the modified TT technique was significantly shorter than in the AM portal technique (p < 0.001). The mean length of the femoral tunnel was significantly longer for the modified TT technique than for the AM portal technique (p < 0.001). The mean coronal angle of the tibial tunnel was significantly lower for the modified TT technique than for the AM portal technique (p < 0.001). The mean coronal angle of the femoral tunnel was significantly lower for the AM portal technique than for the modified TT technique (p < 0.001). The AM portal technique resulted in a graft bending angle that was significantly more angulated in the coronal (p < 0.001) and the sagittal planes (p < 0.001) compared with the modified TT technique. Discussion: Comparison of the preoperative planning and postoperative femoral tunnel positions showed that the mean difference of the tunnel position was 1.8 ± 0.4 mm. It suggested that the surgical navigation robot could make predictable tunnel position with high accuracy. The findings may support that the modified TT technique has benefits on femoral tunnel length and obliquity compared with AM portal technique. The modified TT technique showed a larger femoral tunnel angle in the coronal plane than the AM portal technique. Compared with the modified TT technique, the more horizontal trajectory of the femoral tunnel in the AM portal technique creates a shorter femoral tunnel length and a more acute graft bending angle.